2017
DOI: 10.33961/jecst.2016.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Structure of Ammonium Ions on Capacitance in Electrochemical Double Layer Supercapacitors

Abstract: The conductivity of the electrolyte used plays a critical role in the optimization of the performance of electrochemical double layer capacitors. However, when the difference in the conductivities of different electrolytes is not significant (only 10-20%), the conductivity has little effect on the capacitance. On the other, unlike the conductivity and viscosity of the electrolyte, the cation size directly influences the capacitance. Cyclic ions have a smaller effective radius than that of the corresponding acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The electrode voltage also affects the C d growth rate, the maximum of which always corresponds to the electrode voltage of 1 to 1.5 V. The inverse correlation between C d strength and counter-ion size is consistent with previous studies. [4][5][6][7]17,47 However, the inverse correlation between the C d enhancing rate and the counter-ion size and the nonmonotonicity of the ψ − C s d curve for larger counter-ion size are new findings in this paper.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The electrode voltage also affects the C d growth rate, the maximum of which always corresponds to the electrode voltage of 1 to 1.5 V. The inverse correlation between C d strength and counter-ion size is consistent with previous studies. [4][5][6][7]17,47 However, the inverse correlation between the C d enhancing rate and the counter-ion size and the nonmonotonicity of the ψ − C s d curve for larger counter-ion size are new findings in this paper.…”
Section: Resultsmentioning
confidence: 59%
“…Differential capacitance C d is a measurable quantity in experiments; it can describe responses of electric double layer (EDL) structure to the electrode potential, and plays a key role in determining the energy storage density and energy output mode. Relationship between the C d and other parameters such as electrolyte composition, [1][2][3] ion structure, [4][5][6][7] and temperature, [8][9][10] etc. has become a research focus since a large number of studies [11][12][13][14][15][16][17] have shown that the C d value of the EDLC using ionic liquids or organic ions as working electrolytes obviously increases as the electrode pore tends to order of the ion dimension, and exhibits an oscillatory character with the electrode pore width.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Supercapacitors have attracted research attention owing to the increase in electrical energy consumption in various fields ranging from large to small scale devices such as electric vehicles, portable devices, and smart phones, and this demonstrates that the electrical energy storage devices require high energy and power densities. Thus, extant studies have widely focused on supercapacitors with satisfactory performance including high power density and long cycle stability [5][6][7]. They are utilized in various fields such as energy back-up systems, regenerative braking systems, acceleration in hybrid vehicles, and portable devices that also require energy and power densities.…”
Section: Introductionmentioning
confidence: 99%